Variabilidade de atributos físicos e químicos de solo submetidos a diferentes sistemas de manejo de plantas espontâneas na cafeicultura do cerrado mineiro - Silva, Patrícia Costa (2008)
The cultivation of coffee is in fast development in the Cerrado areas, these areas present soil with favorable physical properties to the development of the coffee cultivation and to mechanization, however in these areas, the soil are very weathered, naturally acid and shows low fertility. With the expansion of the coffee cultivation, new challenges had been incorporated, since that the use of technology and correct handling becomes primordial factors for the maintenance and increase of productivity and profitability. Therefore, the objective of this work was to evaluate the following physical and chemical attributes of the soil: density, microporosity, macroporosity, total porosity, aggregation through the stability of the aggregates by humid way (DMG), total organic carbon, calcium and magnesium, in the coffee grown submitted to different systems of handling of spontaneous plants with different regions of sampling, through the classic statistics and geo-statistics. The area of the research was situated in the Fazenda do Glória UFU- Uberlândia - MG. For sampling of the soil were demarcated four meshes of 1120 m2, contends in each 60 equidistant points of 3 x 4.5 m geo authenticated, in system of dry land and fertirrigated, with control of spontaneous plants by herbicide and disc harrows. In March/2006 (rainy season of the year) and August/2006 (dry season of the year) were removed 480 samples in the depths of 0-20 and 20-40 cm. The samples were removed alternated in the following regions: half of the street, skirt of the coffee plant and tractor traffic line, for each season in order to study the dynamics of all attributes according with Embrapa methodology (1997). The means was compared by test t of Student (0,05 of significance), the analysis of the spatial variability was carried out through semivariograms, obtained for computational program GS+7 for Windows (Gamma Design Software), using the kriging methodology for estimates of the places not sampled. It was verified that the use of herbicides promoted the preservation of the physical and chemical attributes due deposition of remaining vegetal portions on the surface of the soil. The mixing soil, promoted by the use of the disc harrows caused reduction of the density and porosity, reduction of the DMG of the aggregates, increase of the macroporosity and high tax of oxidation of carbon. The skirt of the coffee plant presented highest values of the DMG of aggregates, porosity (macro and micro) and lowest levels of Ca+2 and Mg+2. The tractor traffic line region presented highest values of density, microporosity, Ca+2 and Mg+2 of the soil and lowest values of DMG of aggregates, total porosity and macroporosity of the soil. The results of the geo-statistics analysis indicated spatial dependence for the physical and chemical attributes of the soil. Overall, the mathematical models more adapted to describe the behavior of the semivariograms of attributes of the soil were the Exponential - EXP and the Spherical ESF ones. The EXP model proves the existence of similarity between neighboring points that must be considered in carrying out estimates of values not showed and the ESF model indicates that there is a spatial dependence, the samples for these attributes are correlated between itself.